2016
DOI: 10.1016/j.jmb.2016.07.004
|View full text |Cite
|
Sign up to set email alerts
|

Design Principles for SuCESsFul Biosensors: Specific Fluorophore/Analyte Binding and Minimization of Fluorophore/Scaffold Interactions

Abstract: Quantifying protein location and concentration is critical for understanding function in situ. SuCESsFul biosensors, in which a reporting fluorophore is conjugated to a binding scaffold, can in principle detect analytes of interest with high temporal and spatial resolution. However, their adoption has been limited due to the extensive empirical screening required for their development. We sought to establish design principles for this class of biosensor by characterizing over 400 biosensors based on various pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 59 publications
0
13
0
1
Order By: Relevance
“…Overall, we have demonstrated that libraries based on the charge-neutralized and flattened Sso7d variant rcSso7d yield binders against multiple antigens and epitopes with low nanomolar affinities and beneficial biophysical properties. Recently, rcSso7d-based binders generated in this study were used for the development of highly efficient reagentless biosensors ( 39 ), and a binder that was selected from the rcSso7d-11 library was successfully immobilized on cellulose for the development of paper-based diagnostic tests ( 40 ). We anticipate that the libraries and binders generated in this study will be useful for many other applications, including tumor targeting (hEGFR) and in vivo half-life extension (MSA).…”
Section: Discussionmentioning
confidence: 99%
“…Overall, we have demonstrated that libraries based on the charge-neutralized and flattened Sso7d variant rcSso7d yield binders against multiple antigens and epitopes with low nanomolar affinities and beneficial biophysical properties. Recently, rcSso7d-based binders generated in this study were used for the development of highly efficient reagentless biosensors ( 39 ), and a binder that was selected from the rcSso7d-11 library was successfully immobilized on cellulose for the development of paper-based diagnostic tests ( 40 ). We anticipate that the libraries and binders generated in this study will be useful for many other applications, including tumor targeting (hEGFR) and in vivo half-life extension (MSA).…”
Section: Discussionmentioning
confidence: 99%
“…When the structure of the antigen-complex is known, then this approach of integrating into AgBP of the solvatochromic fluorophore is used to convert into an RF biosensor [18]. Studies have suggested that fluorophore with the tendency of not forming a covalent bond on the surface of bioreceptor can produce RF biosensors of high quality owing to enhance in background signal due to interaction with the binding pocket over the antigen surface [88].…”
Section: Reagentless Fluorescent (Rf) Biosensormentioning
confidence: 99%
“…However, their adoption can be limited due to the extensive experimental screening required for their development. Wittrup’s group recently described their trials to generalize design principle of such “Scaffold conjugated to environment-sensitive fluorophore (SuCESsFul) biosensors” based on various binding protein scaffolds, analytes and fluorescent dyes [ 2 ]. After making more than 400 biosensors, they found that the brightest reading can be obtained when a specific binding pocket for the fluorophore is present on the analyte.…”
Section: Introductionmentioning
confidence: 99%